2019
DOI: 10.5209/esmp.63738
|View full text |Cite
|
Sign up to set email alerts
|

Audiencias y redes: pautas de consumo de industria cultural en España

Abstract: Desde que se registran datos las audiencias televisivas han aumentado progresivamente España. Se acusa una baja en el consumo medio diario de, aproximadamente, cuatro minutos anuales a partir de marzo de 2013. ¿Fenómeno coyuntural de saturación o anuncio de un cambio sustantivo?. Método. La investigación sitúa hermenéuticamente el caso español en el contexto de una sociedad unificada por la globalización de la industria cultural de entretenimiento masivo en un mercado unitario. Para apreciar tendencias, utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…However, we also noted that expansion of the Internet over the last decade means that it is now the primary source of information, ahead of traditional sources such as radio and print media. We also found that traditional and new media are compatible, which means we can also talk about hybrid information sources (Perrin 2015;Núñez Ladevéze et al 2019;Villafañe et al 2020).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, we also noted that expansion of the Internet over the last decade means that it is now the primary source of information, ahead of traditional sources such as radio and print media. We also found that traditional and new media are compatible, which means we can also talk about hybrid information sources (Perrin 2015;Núñez Ladevéze et al 2019;Villafañe et al 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Some conclude that face-to-face communication remains important in rural areas and that citizens also obtain information from local newspapers and television (Miller et al 2012;Warburton et al 2014;Rumata and Sakinah 2020). Some talk about hybrid information and complementary communication (Perrin 2015;Núñez Ladevéze et al 2019;Villafañe et al 2020), while others conclude that the new media are completely changing communication and information supply (Costera Meijer and Groot Kormelink 2014) in rural areas (Kavanaugh et al 2014;Carlsson and Nilsson 2016;Swart et al 2018).…”
Section: Global Citizenship and Information Media In The Rural Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…La teoría del consumo cultural facilita el análisis de cómo estas transformaciones tecnológicas han reconfigurado el panorama mediático y cultural, y cómo la televisión tradicional se ha adaptado para mantener su relevancia en un entorno cada vez más digitalizado (Krolo et al, 2020). También permite identificar las preferencias culturales y dinámicas sociales que influyen en las elecciones de consumo de contenidos audiovisuales, y comprender mejor cómo las audiencias coconstruyen significados y cómo esto influye en la percepción y valoración de los contenidos (Ladevéze et al, 2019).…”
Section: Teoría Del Consumo Culturalunclassified